Negative electrode electrolyte of alkaline total-iron flow battery and preparation method of negative electrode electrolyte
By using ferrous ion complexes prepared by ferrous salt and N,N,N',N'-tetrahydroxyethylethylenediamine and combining air oxidation to prepare iron ion complexes, the problem of iron ion loss and cycle performance of alkaline all-iron flow batteries is solved, and a negative electrode electrolyte with high energy density and stability is achieved, which promotes the commercial application of the battery.
Patent Information
- Application Number
- CN202411690075.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing alkaline all-iron flow batteries have problems of iron ion loss and degradation of cycling performance when high concentration of negative electrode electrolyte, resulting in insufficient energy density and stability.
A complex of ferrous salt and N,N,N',N'-tetrahydroxyethylethylenediamine as ligand was used to stir evenly with the mixed solution of basic components to prepare a negative electrode electrolyte containing ferrous ion complex, and an iron ion complex was prepared by oxidizing oxygen in the air to form a negative electrode electrolyte with high concentration and high stability.
The energy density and cycle stability of alkaline all-iron flow battery are significantly improved, and the theoretical capacity of up to 40.2Ah/L and the actual capacity of 35Ah/L is achieved. Iron and hydrogen evolution are avoided during the charging and discharging process, ensuring the long-term and stable operation of the battery.
Smart Images

Figure CN119650780A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of aqueous liquid flow batteries, and in particular to a negative electrode electrolyte for an alkaline all-iron liquid flow battery and a preparation method thereof. Background Art
[0002] Liquid flow batteries circulate electrolytes in external storage tanks and use redox reactions to release and store energy in the battery stack. They are widely used in renewable energy storage, grid balancing, and large-scale energy management, and are particularly suitable for balancing fluctuations in wind and solar energy. Currently, all-vanadium liquid flow batteries are a more mature type of liquid flow battery, but due to limited vanadium resources, their high cost has constrained the commercialization process. Therefore, it is particularly important to develop new low-cost aqueous liquid flow batteries.
[0003] In addition to all-vanadium flow batteries, the systems that are currently being studied more and are relatively mature include zinc-bromine flow batteries, iron-chromium flow batteries, and zinc-iron flow batteries. In recent years, alkaline all-iron flow batteries have attracted widespread attention due to their low cost, easy access to raw materials, and simple preparation, becoming a potential system for the commercial development of flow batteries.
[0004] Chinese invention patent application CN103700872A discloses an alkaline flow battery with triethanolamine-iron as the negative electrode and o-phenanthroline-iron as the positive electrode. Both the positive and negative electrolytes are iron complex aqueous solutions, which can move the electrode potential of the divalent iron / trivalent iron pair in the positive and negative directions respectively. This new type of all-iron flow battery exhibits good stability and a high open circuit voltage. However, the negative electrode electrolyte of this technology has a solubility of only about 0.4 mol / L, which results in a lower energy density of the battery.
[0005] Chinese invention patent CN112467179B discloses that the negative electrode material is ferric gluconate negative electrode electrolyte, the positive electrode electrolyte is a mixed aqueous solution of ferrocyanide and strong alkali, the concentration of hydroxide in the positive and negative electrode electrolytes is 0.01-8 mol / L, and the concentration of active substances in the positive and negative electrode electrolytes is 0.01-1.5 mol / L. Although the theoretical solubility of this technology can reach about 1.5 mol / L, in actual full battery testing, only 0.8 mol / L can maintain good cycle performance, and when the negative electrode electrolyte reaches 1 mol / L, the cycle performance decreases significantly.
[0006] Chinese invention patent CN 117164485B discloses a complexing agent rich in negative charge, its preparation method and its application in the negative electrode electrolyte of all-iron liquid flow battery; the technology selects suitable amino substances as reaction substrates, and uses a substitution reagent with sulfonate group and an amino-containing substrate to synthesize a complexing agent rich in negative charge through nucleophilic substitution reaction. Although the complexing agent of this technology has high negative electrode solubility, when the complexing agent rich in negative charge is made into the negative electrode electrolyte with iron salt and alkaline components, due to the small solubility product constant of iron hydroxide, when the negative electrode electrolyte is at high concentration, the ionized iron ions and alkaline components are easy to generate iron hydroxide, resulting in a large amount of iron ion loss. After centrifugal filtration, the actual electrolyte concentration is much lower than the theoretical concentration. Summary of the invention
[0008] In view of the stability problem of high concentration of alkaline all-iron liquid flow batteries in the prior art, the purpose of the present invention is to provide a negative electrode electrolyte and a preparation method thereof that can avoid the formation of iron hydroxide when alkaline solution is added during the synthesis process with iron ions as raw materials, reduce iron loss, and form a high-concentration and high-stability negative electrode electrolyte for alkaline all-iron liquid flow batteries, thereby significantly improving the energy density and cycle stability of alkaline all-iron liquid flow batteries.
[0009] The purpose of the invention can be achieved through the following technical solutions: An alkaline all-iron liquid flow battery negative electrode electrolyte, which is a negative electrode electrolyte containing a ferrous ion complex or a negative electrode electrolyte containing a ferric ion complex; The negative electrode electrolyte containing the ferrous ion complex is obtained by uniformly stirring a mixed solution of ferrous salt and ligand with an alkaline solution; the alkaline solution is obtained by mixing an alkaline component with deionized water; the mixed solution of ferrous salt and ligand is obtained by uniformly mixing a ferrous salt solution with a ligand; the ferrous salt solution is obtained by stirring and dissolving a ferrous salt and deionized water; the ligand is N, N, N', N'-tetrahydroxyethylethylenediamine; The negative electrode electrolyte containing the ferric ion complex is obtained by stirring the negative electrode electrolyte containing the ferrous ion complex in the air until the solution turns yellow.
[0010] To further achieve the purpose of the present invention, preferably, the concentration of ferrous ions in the negative electrode electrolyte containing the ferrous ion complex is 0.001-2 mol / L.
[0011] Preferably, the molar ratio of the ligand to the ferrous ion is (1-5):1.
[0012] Preferably, the concentration of the alkaline component in the negative electrode electrolyte containing the ferrous ion complex is 0.5-6 mol / L.
[0013] Preferably, the ferrous salt is one or more of ferrous chloride, ferrous sulfate and ferrous nitrate.
[0014] Preferably, the alkaline component is one or more of potassium hydroxide, sodium hydroxide, lithium hydroxide and barium hydroxide.
[0015] Preferably, the negative electrode electrolyte containing the ferrous ion complex is prepared in a glove box.
[0016] The method for preparing the negative electrode electrolyte of the alkaline all-iron liquid flow battery, the preparation of the negative electrode electrolyte containing the ferrous ion complex comprises the following steps: 1) Stir and dissolve ferrous salt and deionized water to obtain ferrous salt solution; 2) uniformly mixing the solution obtained in step 1) with a ligand to obtain a mixed solution of ferrous salt and ligand; the ligand is N,N,N',N'-tetrahydroxyethylethylenediamine; 3) mixing the alkaline component with deionized water to obtain an alkaline solution; 4) adding the alkaline solution obtained in step 3) to the mixed solution of ferrous salt and ligand obtained in step 2), stirring evenly, to obtain a negative electrode electrolyte containing a ferrous ion complex; The negative electrode electrolyte containing the iron ion complex is obtained by stirring the negative electrode electrolyte containing the ferrous ion complex in the air until the solution turns yellow.
[0017] Preferably, the stirring involved in step 1) to step 4), the stirring involved in the mixing and the stirring involved in the negative electrode electrolyte containing the iron ion complex have a rotation speed of 200-400 rpm.
[0018] Preferably, the time for stirring and dissolving the ferrous salt and deionized water is 0.5-2 hours; Step 4) The stirring time is 1-24 hours;
[0019] The solution turns yellow and then changes from off-white to green and then to yellow.
[0020] Compared with the prior art, the present invention has the following advantages and effects: 1) The present invention uses ferrous ion complexes and ferric ion complexes prepared from divalent iron salts and N,N,N',N'-tetrahydroxyethylethylenediamine as starting materials as the negative electrode electrolyte of the alkaline all-iron liquid flow battery, which has extremely high solubility, and the solubility is as high as 1.5 mol / L when the battery is in stable operation. The theoretical capacity is as high as 40.2 Ah / L. The designed battery operation still has a capacity utilization rate of nearly 90%, and the actual capacity can reach 35Ah / L, realizing a truly high-capacity all-iron liquid flow battery.
[0021] 2) The negative electrode electrolyte prepared by the present invention will not produce iron or hydrogen precipitation during the charge and discharge process. The battery can still operate stably for a long time under high concentration conditions.
[0022] 3) The negative electrode electrolyte prepared by the present invention has a simple preparation process, extremely low cost, and high open circuit voltage, which meets the needs of commercial development of liquid flow batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of a flow battery.
[0025] Figure 2 This is the triethanolamine-iron cyclic voltammetry curve.
[0026] Figure 3 This is the cyclic voltammetry curve of N,N,N',N'-tetrahydroxyethylethylenediamine-iron.
[0027] Figure 4 This is a test diagram of the symmetrical battery cycle performance of Example 1.
[0028] Figure 5 This is a test diagram of the symmetrical battery cycle performance of Example 2.
[0029] Figure 6 This is a test diagram of the battery cycle performance of Example 3.
[0030] Figure 7 This is a battery cycle test diagram of Example 4.
[0031] Figure 8 This is the battery cycle test diagram of comparative example 1. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The invention is characterized in that N, N, N', N'-tetrahydroxyethylethylenediamine is used as a ligand, and a ferrous ion complex is synthesized using ferrous salt as an initial raw material by utilizing the huge difference in the solubility product constant between ferrous hydroxide and ferric hydroxide, and the ferric ion complex is prepared by oxidation through oxygen in the air. As for the ferrous salt, the specific selection of the alkaline component can be easily obtained according to the purpose of the invention; as for the ferrous salt, the specific amount of the alkaline component and the ligand can be obtained through experiments in combination with the purpose of the invention, and the concentration of ferrous ions in the negative electrode electrolyte containing the ferrous ion complex is preferably 0.001-2 mol / L. The molar ratio of the ligand to the ferrous ion is (1-5): 1. The concentration of the alkaline component in the negative electrode electrolyte containing the ferrous ion complex is 0.5-6 mol / L. The preparation of the negative electrode electrolyte containing the ferrous ion complex in the present invention is preferably carried out in a glove box, or in any airtight environment isolated from air.
[0034] The cyclic voltammetry test conditions used in this embodiment and comparative example are: a three-electrode system is adopted, the working electrode is a glassy carbon electrode, the counter electrode is a platinum wire, the reference electrode is silver / silver chloride, the scan rate is 50 mV / s, and the negative scan is from -0.75V to -1.4V, and the cycle is 20 times.
[0035] The battery test conditions used in this embodiment and comparative example are: a flow battery device composed of an end plate, a fluororubber pad, a graphite plate, an electrode frame, a porous carbon felt, a proton exchange membrane, and a diaphragm pump is used for testing. The principle is as follows: Figure 1 As shown, the specific test conditions are set in detail in each embodiment and comparative example.
[0036] Example 1 (Non-isovolume symmetric battery with a total iron concentration of 1 mol / L and 2 times the ligand)
[0037] A method for preparing an electrolyte for an alkaline all-iron flow battery comprises the following steps: 1) Add 2.54 g of ferrous chloride and 3 mL of deionized water into a stirred reactor and stir at 200 rpm for 0.5 h; 2) Slowly add 9.44 g of ligand N,N,N',N'-tetrahydroxyethylethylenediamine to the solution in step 1) while stirring, make the volume to 10 mL, and continue stirring at 200 rpm for 2 hours; 3) Dissolve 4 g of the alkaline component sodium hydroxide in deionized water and make up to 10 mL, then stir at 200 rpm for 0.5 h until the solution becomes clear, and cool to room temperature; 4) Slowly add the solution obtained in step 3) to the solution obtained in step 2), and stir continuously at 300 rpm for 2 hours to obtain 20 mL of negative electrode electrolyte containing ferrous ion complex with a concentration of 1 mol / L; 5) Take 10 mL of the negative electrode electrolyte containing the ferrous ion complex obtained in step 4) and transfer it to the air and stir it continuously at 300 rpm until the solution changes from grayish white to green and then to yellow, thereby preparing 10 mL of the negative electrode electrolyte containing 1 mol / L ferric ion complex.
[0038] Take 7 mL of the ferrous ion complex electrolyte obtained in step 4) and 7 mL of the ferric ion complex electrolyte obtained in step 5), and mix them thoroughly to prepare a total of 14 mL of symmetrical battery electrolyte.
[0039] The symmetrical battery electrolyte was divided into two bottles of 6 mL and 8 mL for symmetrical battery cycle testing. The positive and negative electrodes of the conditional flow battery were 4 mm thick porous carbon felt electrodes with an area of 6 cm 2 ; The current collecting plate is made of graphite plate; the ion conducting membrane is commercially available Nafion212 membrane with an effective area of 6 cm 2 ; Charge and discharge under the condition of 30 current density, the cut-off voltage of forward electrolysis is 0.7 V, and the cut-off voltage of reverse electrolysis is - 0.7 V. Under such conditions, the coulomb efficiency of the battery is 99%, and the battery capacity does not decay after 160 cycles. Figure 4 shown.
[0040] Example 2 (symmetric cell with equal volume and total iron concentration of 1.5 mol / L and 1.5 times ligand)
[0041] A method for preparing an electrolyte for an alkaline all-iron flow battery comprises the following steps: 1) Add 3.81 g of ferrous chloride and 3 mL of deionized water into a stirred reactor and stir at 200 rpm for 0.5 h. 2) Slowly add 10.62 g of ligand N,N,N',N'-tetrahydroxyethylethylenediamine to the solution in step 1) while stirring, make the volume to 10 mL, and continue stirring at 200 rpm for 2.5 hours; 3) Dissolve 4.8 g of the alkaline component sodium hydroxide in deionized water and make up to 10 mL, then stir at 200 rpm for 0.5 h until the solution becomes clear, and cool to room temperature; 4) Slowly add the solution obtained in step 3) to the solution obtained in step 2), and stir continuously at 400 rpm for 5 hours to obtain 20 mL of negative electrode electrolyte containing ferrous ion complex at a concentration of 1.5 mol / L; 5) Take 10 mL of the negative electrode electrolyte containing the ferrous ion complex obtained in step 4) and transfer it to the air and stir it continuously at 400 rpm until the solution changes from grayish white to green and then to yellow, thereby preparing 10 mL of the negative electrode electrolyte containing 1.5 mol / L ferric ion complex.
[0042] Take 8 mL of the ferrous ion complex electrolyte obtained in step 4) and 8 mL of the ferric ion complex electrolyte obtained in step 5), and mix them thoroughly to prepare a total of 16 mL of symmetrical battery electrolyte.
[0043] The symmetrical battery electrolyte was divided into two bottles of 8 mL and 8 mL for symmetrical battery cycle testing. The positive and negative electrodes of the conditional flow battery were 4 mm thick porous carbon felt electrodes with an area of 48 cm 2 ; The current collector is made of graphite plate; the ion conduction membrane is the commercially available Nafion212 membrane; the charge and discharge are performed at a current density of 33, the forward electrolysis cutoff voltage is 0.7 V, and the reverse electrolysis cutoff voltage is - 0.7 V. Under such conditions, the coulomb efficiency of the battery is 99.95%, and the battery capacity has not decayed after 110 cycles. Figure 5 .
[0044] Example 3 (Total iron concentration at 0.2 mol / L, 2-fold ligand full cell test)
[0045] A method for preparing an electrolyte for an alkaline all-iron flow battery comprises the following steps: 1) Add 0.178 g of ferrous chloride and 2 mL of deionized water into a stirred reactor and stir at 200 rpm for 30 min; 2) Slowly add 0.66 g of ligand N,N,N',N'-tetrahydroxyethylethylenediamine to the solution in step 1) while stirring, make the volume to 4 mL, and continue stirring at 200 rpm for 1 hour; 3) Dissolve 0.84 g of the alkaline component sodium hydroxide in deionized water and adjust the volume to 3 mL, then stir at 200 rpm for 0.5 h until the solution becomes clear, and cool to room temperature; 4) Slowly add the solution obtained in step 3) to the solution obtained in step 2), and stir continuously at 400 rpm for 3 hours to obtain 7 mL of negative electrode electrolyte containing ferrous ion complex at a concentration of 0.2 mol / L;
[0046] A method for preparing a positive electrode electrolyte for an alkaline all-iron liquid flow battery comprises the following steps: Add 6 g of sodium hydroxide and 40 mL of deionized water into a stirred reactor and stir at 200 rpm until it becomes clear; Weigh 4.22 g of potassium ferrocyanide trihydrate and 3.29 g of potassium ferrocyanide and add them to the solution in step 1), stir to dissolve and then dilute to 50 mL to obtain a positive electrode electrolyte with a composition of 0.2 mol / L potassium ferrocyanide and 0.2 mol. / L potassium ferrocyanide.
[0047] like Figure 3 As shown, the negative electrode electrolyte was first subjected to a cyclic voltammetry test. The results showed that the negative electrode electrolyte still maintained good redox reversibility after 20 cycles of cyclic voltammetry.
[0048] The flow battery is composed of a potassium ferrocyanide positive electrolyte and a ferrous ion complex-containing negative electrolyte. The positive and negative electrodes of the battery are both 4 mm porous carbon felt electrodes with an area of 6 cm 2 The current collecting plate is made of graphite plate, and the ion conducting membrane is the commercially available Nafion212 membrane.
[0049] Test conditions: at 80 mA / cm 2 The battery was charged at a constant current density of 1.45 V, then charged at a constant voltage of 1.45 V until the cut-off current reached 10 mA, and discharged at 80 mA / cm 2 The battery was discharged at a constant current density of 0.4 V to 0.4 V, and then discharged at a constant voltage of 0.4 V to a cut-off current of 10 mA, and cycled 100 times under such conditions. The test results show that the average coulombic efficiency, energy efficiency, and voltage efficiency of the battery are 99.87%, 77.37%, and 77.47%, respectively. The cycle performance is stable and decays slowly, with an average decay of 0.0348% per cycle. Figure 6 shown.
[0050] Example 4 (Total iron concentration at 1 mol / L, 2-fold ligand full cell test)
[0051] A method for preparing an electrolyte for an alkaline all-iron flow battery comprises the following steps: 1) Add 0.89 g of ferrous chloride and 2 mL of deionized water into a stirred reactor and stir at 200 rpm for 1 h; 2) Slowly add 3.3 g of ligand N,N,N',N'-tetrahydroxyethylethylenediamine to the solution in step 1) while stirring, make the volume to 4 mL, and continue stirring at 200 rpm for 2 hours; 3) Dissolve 1.4 g of the alkaline component sodium hydroxide in deionized water and adjust the volume to 3 mL, then stir at 200 rpm for 0.5 h until the solution becomes clear, and cool to room temperature; 4) Slowly add the solution obtained in step 3) to the solution obtained in step 2), and stir continuously at 400 rpm for 4 hours to obtain 7 mL of negative electrode electrolyte containing ferrous ion complex at a concentration of 1 mol / L;
[0052] The method for preparing the positive electrode electrolyte of the alkaline all-iron liquid flow battery of this embodiment comprises the following steps: 40 g of sodium hydroxide and 180 mL of deionized water were added to a stirred reactor and stirred at 200 rpm until clear; Weigh 4.22 g of potassium ferrocyanide trihydrate and 19.74 g of potassium ferrocyanide and add them to the solution in step 1), stir to dissolve and then dilute to 200 mL to obtain a positive electrode electrolyte with a composition of 0.3 mol / L potassium ferrocyanide and 0.05 mol. / L potassium ferrocyanide; The positive and negative electrodes of the flow battery are both 4 mm porous carbon felt electrodes with an area of 6 cm 2 The current collecting plate is made of graphite plate, and the ion conducting membrane is the commercially available Nafion212 membrane.
[0053] The test conditions are: charging at a constant current density of 50 mA / cm2 to 1.5 V, then charging at a constant voltage of 1.5 V until the cut-off current is 100 mA, discharging at a constant current density of 50 mA / cm2 to 0.4 V, and then discharging at a constant voltage of 0.4 V to a cut-off current of 100 mA. After 100 cycles under such conditions, the average coulombic efficiency, energy efficiency, and voltage efficiency of the battery are 99.3%, 83.7%, and 84.3%, respectively. The cycle performance is stable and decays slowly, with an average decay of 0.0026% per cycle. Figure 6 shown.
[0054] Example 5 (Full-cell test with total ferrous sulfate concentration of 0.2 mol / L, 2-fold ligand, and potassium hydroxide as base)
[0055] A method for preparing an electrolyte for an alkaline all-iron flow battery comprises the following steps: 1) Add 0.389 g of ferrous chloride and 2 mL of deionized water into a stirred reactor and stir at 200 rpm for 30 min; 2) Slowly add 0.66 g of ligand N,N,N',N'-tetrahydroxyethylethylenediamine to the solution in step 1) while stirring, make the volume to 4 mL, and continue stirring at 200 rpm for 1 hour; 3) Dissolve 1.18 g of the alkaline component sodium hydroxide in deionized water and adjust the volume to 3 mL, then stir at 200 rpm for 0.5 h until the solution becomes clear, and cool to room temperature; 4) Slowly add the solution obtained in step 3) to the solution obtained in step 2), and stir continuously at 400 rpm for 3 hours to obtain 7 mL of negative electrode electrolyte containing ferrous ion complex at a concentration of 0.2 mol / L;
[0056] The method for preparing the positive electrode electrolyte of the alkaline all-iron liquid flow battery of this embodiment comprises the following steps: 8.4 g potassium hydroxide and 40 mL deionized water were added to a stirred reactor and stirred at 200 rpm until clear; Weigh 4.22 g potassium ferrocyanide trihydrate and 3.29 g potassium ferrocyanide and add them to the solution in step 1), stir to dissolve and then dilute to 50 mL to obtain a positive electrode electrolyte with a composition of 0.2 mol / L potassium ferrocyanide and 0.2 mol. / L potassium ferrocyanide; The obtained positive and negative electrolytes are used to form a liquid flow battery. The positive and negative electrodes of the battery are both 4 mm porous carbon felt electrodes with an area of 6 cm 2 The current collecting plate is made of graphite plate, and the ion conducting membrane is the commercially available Nafion212 membrane.
[0057] Test conditions: at 80 mA / cm 2 The battery was charged at a constant current density of 1.45 V, then charged at a constant voltage of 1.45 V until the cut-off current reached 10 mA, and discharged at 80 mA / cm 2 The battery was discharged at a constant current density of 0.4 V to 0.4 V, and then discharged at a constant voltage of 0.4 V to a cut-off current of 10 mA, and cycled 100 times under such conditions. The test results show that the average coulomb efficiency, energy efficiency, and voltage efficiency of the battery are 99.85%, 76.21%, and 76.32%, respectively. The cycle performance is stable and decays slowly, with an average decay of 0.037% per cycle.
[0058] Comparative Example 1 (Total iron concentration of 0.2 mol / L, 2-fold triethanolamine ligand full battery test)
[0059] The preparation method of the negative electrode electrolyte of the comparative alkaline all-iron flow battery is as follows: 1) Add 0.178 g of ferrous chloride and 2 mL of deionized water into a stirred reactor and stir at 200 rpm for 30 min; 2) Slowly add 0.42 g of triethanolamine to the solution in step 1) while stirring, make the volume 4 mL, and continue stirring at 200 rpm for 1 hour; 3) Dissolve 0.84 g of the alkaline component sodium hydroxide in deionized water and adjust the volume to 3 mL, then stir at 200 rpm for 0.5 h until the solution becomes clear, and cool to room temperature; 4) Slowly add the solution obtained in step 3) into the solution obtained in step 2), and stir continuously at 400 rpm for 3 hours to obtain 7 mL of negative electrode electrolyte containing triethanolamine-ferrous iron complex with a concentration of 0.2 mol / L;
[0060] The preparation method of the positive electrode electrolyte of the alkaline all-iron flow battery of this comparative example is as follows: 1) Add 6 g of sodium hydroxide and 40 mL of deionized water into a stirred reactor and stir at 200 rpm until the solution becomes clear. 2) Weigh 4.22 g potassium ferrocyanide trihydrate and 3.29 g potassium ferrocyanide and add them to the solution in step 1), stir to dissolve and then dilute to 50 mL to obtain a positive electrolyte solution with a composition of 0.2 mol / L potassium ferrocyanide and 0.2 mol. / L potassium ferrocyanide;
[0061] like Figure 2 As shown, first, a cyclic voltammetry test was performed on the triethanolamine-ferrous iron negative electrode electrolyte. The results showed that after 20 cycles of cyclic voltammetry, the negative electrode electrolyte had a reduction peak of iron precipitation, and iron element obviously appeared at the glassy carbon electrode.
[0062] Then, a flow battery was formed using a negative electrolyte containing triethanolamine-ferrous iron complex and a positive electrolyte containing potassium ferrocyanide. The positive and negative electrodes of the battery were both 4 mm porous carbon felt electrodes with an area of 6 cm2, a graphite plate was used for the current collector, and a commercially available Nafion212 membrane was used for the ion conduction membrane.
[0063] The test conditions are: charge to 1.45 V at a constant current density of 80 mA / cm2, then charge at a constant voltage of 1.45 V until the cut-off current is 10 mA, discharge at a constant current density of 80 mA / cm2 to 0.4 V, then discharge at a constant voltage of 0.4 V to a cut-off current of 10 mA, and cycle 100 times under such conditions. The test results show that the coulomb efficiency, energy efficiency, and voltage efficiency of the battery are 99.80%, 82.55%, and 82.71% respectively. The average attenuation per cycle is 0.0625%, the cycle is unstable, and the attenuation is serious, such as Figure 8 shown.
[0064] The above test results show that the 0.2-1.5 mol / L negative electrode prepared by the ligand and synthesis method of the present invention has high chemical stability and electrochemical stability. More importantly, compared with the rapid attenuation of triethanolamine iron in the low-concentration full battery test experiment, the complex synthesized by the ligand and preparation method used in the present invention can still maintain good cycle performance in low-concentration and high-concentration battery tests, achieving a theoretical capacity of up to 40.2Ah / L and an actual capacity of 35Ah / L, which is conducive to promoting the commercial application of alkaline all-iron liquid flow batteries.
Claims
1. An alkaline all-iron liquid flow battery negative electrode electrolyte, characterized in that: It is a negative electrode electrolyte containing a ferrous ion complex or a negative electrode electrolyte containing a ferric ion complex; The negative electrode electrolyte containing the ferrous ion complex is obtained by uniformly stirring a mixed solution of ferrous salt and ligand with an alkaline solution; the alkaline solution is obtained by mixing an alkaline component with deionized water; the mixed solution of ferrous salt and ligand is obtained by uniformly mixing a ferrous salt solution with a ligand; the ferrous salt solution is obtained by stirring and dissolving a ferrous salt and deionized water; the ligand is N, N, N', N'-tetrahydroxyethylethylenediamine; The negative electrode electrolyte containing the ferric ion complex is obtained by stirring the negative electrode electrolyte containing the ferrous ion complex in the air until the solution turns yellow.
2. The negative electrode electrolyte of the alkaline all-iron liquid flow battery according to claim 1, characterized in that: The concentration of ferrous ions in the negative electrode electrolyte containing the ferrous ion complex is 0.001-2 mol / L.
3. The negative electrode electrolyte of the alkaline all-iron liquid flow battery according to claim 1, characterized in that: The molar ratio of the ligand to the ferrous ion is (1-5):
1.
4. The negative electrode electrolyte of the alkaline all-iron liquid flow battery according to claim 1, characterized in that: The concentration of the alkaline component in the negative electrode electrolyte containing the ferrous ion complex is 0.5-6 mol / L.
5. The negative electrode electrolyte of the alkaline all-iron liquid flow battery according to claim 1, characterized in that: The ferrous salt is one or more of ferrous chloride, ferrous sulfate and ferrous nitrate.
6. The negative electrode electrolyte of the alkaline all-iron liquid flow battery according to claim 1, characterized in that: The alkaline component is one or more of potassium hydroxide, sodium hydroxide, lithium hydroxide and barium hydroxide.
7. The negative electrode electrolyte of the alkaline all-iron liquid flow battery according to claim 1, characterized in that: The negative electrode electrolyte containing the ferrous ion complex is prepared in a glove box.
8. The method for preparing the negative electrode electrolyte of the alkaline all-iron liquid flow battery according to claim 1, characterized in that: The preparation of the negative electrode electrolyte containing the ferrous ion complex comprises the following steps: 1) Stir and dissolve ferrous salt and deionized water to obtain ferrous salt solution; 2) uniformly mixing the solution obtained in step 1) with a ligand to obtain a mixed solution of ferrous salt and ligand; the ligand is N,N,N',N'-tetrahydroxyethylethylenediamine; 3) mixing the alkaline component with deionized water to obtain an alkaline solution; 4) adding the alkaline solution obtained in step 3) to the mixed solution of ferrous salt and ligand obtained in step 2), stirring evenly, to obtain a negative electrode electrolyte containing a ferrous ion complex; The negative electrode electrolyte containing the iron ion complex is obtained by stirring the negative electrode electrolyte containing the ferrous ion complex in the air until the solution turns yellow.
9. The method for preparing the negative electrode electrolyte of the alkaline all-iron liquid flow battery according to claim 8, characterized in that: The stirring involved in the steps 1) to 4), the stirring involved in the mixing, and the stirring involved in the negative electrode electrolyte containing the iron ion complex have a rotation speed of 200-400 rpm.
10. The method for preparing the negative electrolyte of the alkaline all-iron liquid flow battery according to claim 8, characterized in that: The time for stirring and dissolving the ferrous salt and deionized water is 0.5-2 hours; Step 4) The stirring time is 1-24 hours; The solution turns yellow and then changes from off-white to green and then to yellow.
Citation Information
Patent Citations
Total-iron complexing flow cell with high open-circuit voltage
CN103700872A
An alkaline all-iron flow battery
CN112467179B
A complexing agent rich in negative charge, preparation method thereof and application thereof in negative electrode electrolyte of all-iron liquid flow battery
CN117164485B
Electrolyte of water-based flow battery, all-iron water-based flow battery and application
CN113764714A
Alkaline negative electrode electrolyte of high-stability iron-based flow battery
CN118712441A